The dog I loved [large type] - Wilson, Susan, 1951- (Thorndike Press large print basic, 2019)
"Can a dog lead the way to finding one's humanity? After spending years in prison for a crime she didn't intend to commit, Rose Collins is suddenly free. Someone who knows about the good work she has done--training therapy dogs while serving time--has arranged for her early release. This benefactor has even set her up with a job in the Massachusetts community of Gloucester. Meghan Custer is a wheelchair-bound war veteran. Ever since she was matched with a service dog named Shark, she can live on her own. And maybe, with Shark by her side, even find love again. Two strong women on a journey toward independence whose paths collide in extraordinary ways."--Provided by publisher.